PKMS PEMBERDAYAAN IBU RUMAH TANGGA BERBASIS EKONOMI KREATIF MELALUI USAHA PEMBUATAN KUE TRADISIONAL DI BANJAR BLAHTANAH SUKAWATI - Putu Dian Pradnyanitasari; Putu Yudha Asteria Putri; Ida Ayu Agung Idawati (Universitas Kadiri, 2019)
Market snacks are foods that are usually bought from traditional markets. Until now the market snacks are still very popular for family snacks and served to guests. One type of market snacks that are well known from any times to the present is the sagon cake. In Bali the sagon cake which is commonly called